2015
DOI: 10.1002/adfm.201500299
|View full text |Cite
|
Sign up to set email alerts
|

2D and 3D Hybrid Systems for Enhancement of Chondrogenic Differentiation of Tonsil‐Derived Mesenchymal Stem Cells

Abstract: 2D/3D hybrid cell culture systems are constructed by increasing the temperature of the thermogelling poly(ethylene glycol)‐poly(l‐alanine) diblock copolymer (PEG‐l‐PA) aqueous solution in which tonsil tissue‐derived mesenchymal stem cells and graphene oxide (GO) or reduced graphene oxide (rGO) are suspended, to 37 °C. The cells exhibit spherical cell morphologies in 2D/3D hybrid culture systems of GO/PEG‐l‐PA and rGO/PEG‐l‐PA by using the growth medium. The cell proliferations are 30%–50% higher in the rGO/PEG… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
53
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 71 publications
(55 citation statements)
references
References 48 publications
2
53
0
Order By: Relevance
“…[11][12][13] Stem cell engineering using the graphene or chemically exfoliated graphene oxide (GO) has been investigated as one such potential biomedical application, due to its physicochemical and electrical properties that allow control of cellular behaviors (e.g., adhesion, proliferation, differentiation, polarization, and paracrine secretion) and biocompatibility. [14][15][16][17][18] Previous studies have reported enhanced adhesion, proliferation, and differentiation of mesenchymal stem cells on graphene or GO substrates based on their chemical properties and their patterning. 12,19 In addition, it has been demonstrated that the differentiation of neural stem cells (NSCs), which are sensitive to electrical signal, could be promoted on the surface of graphene or GO substrates due to their electrical properties.…”
Section: Introductionmentioning
confidence: 99%
“…[11][12][13] Stem cell engineering using the graphene or chemically exfoliated graphene oxide (GO) has been investigated as one such potential biomedical application, due to its physicochemical and electrical properties that allow control of cellular behaviors (e.g., adhesion, proliferation, differentiation, polarization, and paracrine secretion) and biocompatibility. [14][15][16][17][18] Previous studies have reported enhanced adhesion, proliferation, and differentiation of mesenchymal stem cells on graphene or GO substrates based on their chemical properties and their patterning. 12,19 In addition, it has been demonstrated that the differentiation of neural stem cells (NSCs), which are sensitive to electrical signal, could be promoted on the surface of graphene or GO substrates due to their electrical properties.…”
Section: Introductionmentioning
confidence: 99%
“…Previous reports have confirmed using graphene as a cell differentiation controlling biomaterial, especially for neurogenesis and osteogenesis on 2D substrates . GO has been considered as a carrier for therapeutic proteins due to its highly biocompatible and low cytoxicity effects . Nayak and colleagues found an uncommon behavior of osteoblast cells using graphene coated on SiO 2 /Si substrate …”
Section: Introductionmentioning
confidence: 94%
“…Additionally, graphene‐containing polymer hydrogel due to its biocompatibility can be used as biosensor, imaging agent, drug delivery carrier, etc . In particular, GO is an effective component in the composite hydrogel for the adjustment of cell behaviors and biological sequences due to its special surface properties.…”
Section: Properties and Applications Of Polymer–graphene Hydrogelsmentioning
confidence: 99%